Industri 4.0 dan Kinerja Perusahaan Telekomunikasi yang Terdaftar di BEI - Fazahra, Syafina; Masdupi, Erni (Dinasti Review, 2025)
Currently, Indonesia as one of the developing countries, is gradually transitioning toward the adoption of technology in the era of Industry 4.0, as demonstrated by the government’s “Making Indonesia 4.0” program, which serves as an acceleration initiative to enter the industrial revolution era and aims to position Indonesia among the world’s top 10 economies by 2030. This highlights the importance of adapting to the industrial revolution in a dynamic business environment. This study aims to examine the influence of Industry 4.0 on firm performance with servitization and leverage as intervening variables in telecommunications companies listed on the Indonesia Stock Exchange. This is a quantitative study, and the sampling method used is non-probability sampling based on purposive sampling. The sample consists of 152 data points derived from telecommunications companies listed on the Indonesia Stock Exchange. Data analysis was conducted using path analysis with IBM SPSS Amos 21 software. The results of this study show that Industry 4.0 has a significant positive effect on firm performance and servitization, while servitization has a significant negative effect on firm performance. Industry 4.0 has a positive but not significant effect on leverage, and leverage also has no significant effect on firm performance. Servitization is able to mediate the relationship between Industry 4.0 and firm performance, whereas leverage does not.